Dugaan Predatory Pricing Pada Promosi Flash Sale: Dimana Peran KPPU? - Andini, Septian Dwi; Hidayah, Astika Nurul (JURNAL PENELITIAN SERAMBI HUKUM, 2024)
The impact of the rapid progress of e-commerce in Indonesia, especially in the practice of Flash Sale promotions by significantly reducing prices in a limited time, raises concerns regarding the alleged predatory pricing practices that cause unfair business competition. The role of the Business Competition Supervisory Commission (KPPU) is crucial in preventing potential violations of Law Number 5 Year 1999 on the Prohibition of Monopolistic Practices and Unfair Business Competition in the e-commerce sector. The purpose of this study is to determine and analyze the application of the rule of reason approach by KPPU in the case of alleged predatory pricing practices in flash sale promotion strategies on e-commerce sites and how the role of KPPU in preventing alleged predatory pricing practices on e-commerce sites. The research method used is Normative Law with statute, conceptual, and case approaches. The results of this study show that KPPU uses a rules of reason approach by considering factors such as production costs, price motivation, and the impact on competitors and the market so that the analysis shows that flash sale practices, although offering prices far below the market, cannot be considered as predatory pricing that harms business competition. KPPU's role in efforts to prevent predatory pricing practices in e-commerce has established a Prevention Deputy that acts as a digital referee, overseeing business activities and while overseeing predatory pricing.